Open data: The early but not the late neural correlate of auditory awareness reflects lateralized experiences - Wiens, Stefan; Eklund, Rasmus; Gerdfeldter, Billy (Stockholm University, 2021)
GENERAL INFORMATION

1. Title of Dataset:
Open data: The early but not the late neural correlate of auditory awareness reﬂects lateralized experiences.

2. Author Information
A. Principal Investigator Contact Information
Name: Stefan Wiens
Institution: Department of Psychology, Stockholm University, Sweden
Internet: https://www.su.se/profiles/swiens-1.184142
Email: sws@psychology.su.se

B. Associate or Co-investigator Contact Information
Name: Rasmus Eklund
Institution: Department of Psychology, Stockholm University, Sweden
Internet: https://www.su.se/profiles/raek2031-1.223133
Email: rasmus.eklund@psychology.su.se

C. Associate or Co-investigator Contact Information
Name: Billy Gerdfeldter
Institution: Department of Psychology, Stockholm University, Sweden
Internet: https://www.su.se/profiles/bige1544-1.403208
Email: billy.gerdfeldter@psychology.su.se

3. Date of data collection:
Subjects (N = 28) were tested between 2020-03-04 and 2020-09-18.

4. Geographic location of data collection: Department of Psychology, Stockholm, Sweden

5. Information about funding sources that supported the collection of the data:
Marianne and Marcus Wallenberg (Grant 2019-0102)

SHARING/ACCESS INFORMATION

1. Licenses/restrictions placed on the data: CC BY 4.0

2. Links to publications that cite or use the data: Eklund R., Gerdfeldter B., & Wiens S. (2021). The early but not the late neural correlate of auditory awareness reﬂects lateralized experiences. Neuropsychologia. https://doi.org/

The study was preregistered:
https://doi.org/10.17605/OSF.IO/PSRJF

3. Links to other publicly accessible locations of the data: N/A

4. Links/relationships to ancillary data sets: N/A

5. Was data derived from another source? No

6. Recommended citation for this dataset: Eklund R., Gerdfeldter B., & Wiens S. (2020). Open data: The early but not the late neural correlate of auditory awareness reﬂects lateralized experiences. Stockholm: Stockholm University. https://doi.org/10.17045/sthlmuni.13067018

DATA & FILE OVERVIEW

File List:
The files contain the downsampled data in bids format, scripts, and results of main and supplementary analyses of the electroencephalography (EEG) study. Links to the hardware and software are provided under methodological information.

AAN_LRclick_experiment_scripts.zip: contains the Python files to run the experiment

AAN_LRclick_bids_EEG.zip: contains EEG data files for each subject in .eeg format.

AAN_LRclick_behavior_log.zip: contains log files of the EEG session (generated by Python)

AAN_LRclick_EEG_scripts.zip: Python-MNE scripts to process and to analyze the EEG data

AAN_LRclick_results.zip: contains summary data files, figures, and tables that are created by Python-MNE.

METHODOLOGICAL INFORMATION

1. Description of methods used for collection/generation of data:
The auditory stimuli were 4-ms clicks.
The experiment was programmed in Python: https://www.python.org/ and used extra functions from here: https://github.com/stamnosslin/mn
The EEG data were recorded with an Active Two BioSemi system (BioSemi, Amsterdam, Netherlands; www.biosemi.com) and converted to .eeg format.
For more information, see linked publication.

2. Methods for processing the data:
We computed event-related potentials. See linked publication

3. Instrument- or software-specific information needed to interpret the data:
MNE-Python (Gramfort A., et al., 2013): https://mne.tools/stable/index.html#

4. Standards and calibration information, if appropriate:
For information, see linked publication.

5. Environmental/experimental conditions:
For information, see linked publication.

6. Describe any quality-assurance procedures performed on the data:
For information, see linked publication.

7. People involved with sample collection, processing, analysis and/or submission:

- Data collection: Rasmus Eklund with assistance from Billy Gerdfeldter.
- Data processing, analysis, and submission: Rasmus Eklund

DATA-SPECIFIC INFORMATION:
All relevant information can be found in the MNE-Python scripts (in EEG_scripts folder) that process the EEG data. For example, we added notes to explain what different variables mean.

The folder structure needs to be as follows:
AAN_LRclick (main folder)
--->data
--->--->bids (AAN_LRclick_bids_EEG)
--->--->log (AAN_LRclick_behavior_log)
--->MNE (AAN_LRclick_EEG_scripts)
--->results (AAN_LRclick_results)

To run the MNE-Python scripts:
Anaconda was used with MNE-Python 0.22 (see installation at https://mne.tools/stable/index.html# ).
For preprocess.py and analysis.py, the complete scripts should be run (from anaconda prompt).
Keywords: 170101 Biological Psychology (Neuropsychology, Psychopharmacology, Physiological Psychology); Neuroscience and Physiological Psychology; Neurosciences; Neurovetenskaper; Biological Sciences; Biologi